Diflexx Duo Compared to Capreno, Halex GT, Armezon, Outlook, Status, Degree Xtra, and Bicep II Magnum for Weed Control in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Control of kochia, quinoa, and green foxtail was complete with all herbicides at 78 days after treatment (DAT). Palmer amaranth, common sunflower, and crabgrass was 97% at 8 DAT. By 78 DAT, common sunflower control was complete with all herbicides. Crabgrass control at 78 DAT was excellent except when Diflexx Duo (dicamba + tembotrione) at 24 oz/a + atrazine was mixed with glyphosate or Liberty. All herbicide-treated corn yielded 111 to 126 bu/a more grain than the untreated controls. The various additions to the premixes improved weed control to the point that no difference occurred among them for yield.
Keywords: Single application; residual control